PENERAPAN METODE TALKING STICK UNTUK MENINGKATKAN KEAKTIFAN BELAJAR PADA PESERTA DIDIK - Peni, Petronela; Keban , Yosep Belen; Bura , Herman Lorenzo (JAPB: Jurnal Agama, Pendidikan dan Budaya, 2026)
Learning activity is one of the important factors that support the success of the learning process because it influences student participation and understanding. However, in Church History learning in class XI A SMAK St. Yakobus Rasul Lewoleba, the level of student activity is still relatively low, which is seen from the lack of involvement in asking, answering questions, and expressing opinions. This study aims to improve student learning activity through the application of the Talking Stick method. The study was conducted at SMAK St. Yakobus Rasul Lewoleba using a Classroom Action Research (CAR) approach consisting of two cycles, namely planning, implementing actions, observation, and reflection. The subjects of the study were all 19 students of class XI A at SMAK St. Yakobus Rasul Lewoleba. Data were collected through observation and documentation, then analyzed descriptively qualitatively. The results of the study indicate that the application of the Talking Stick method can improve student learning activity, which is characterized by increased courage in answering questions, expressing opinions, and actively participating in discussions during the learning process.